Clinical Supervision for Support Workers in Paediatric Palliative Care: A Literature Review. (January 2021) - Beavis, Jonathan; Davis, Lucy; McKenzie, Sian
Providing home care to children with complex physical health needs is an emotionally challenging role. Extant literature and documents such as the Cavendish Review (2013) have reported that a large proportion of care for this population is carried out by non-registered staff (support workers). Provision of clinical supervision for nurses working in palliative care is increasing, however, supervision needs of support workers are commonly neglected. This paper sought to synthesise what is known about clinical supervision practices for support workers in paediatric palliative care (PPC). A literature review was conducted in accordance with integrative review guidelines. 315 papers were identified initially, 15 studies were included in this review. Four commonalities were identified: importance of team cohesion, varying degrees of formality, self-awareness and practicalities. Support workers received varying forms of supervision and some facilitators faced organisational difficulties involving staff in supervision. Support workers who received staff support generally appreciated it in recognition that their work is complex and emotionally difficult. This paper highlighted that further research should investigate the efficacy of clinical supervision as a method of reducing stress and burnout for support workers. Any implementation of supervision should involve a considered approach to training and supervision to ensure fidelity.